(untitled) (Global Journal of Science Frontier Research, 2013)
The present study reveals with seasonal analysis of various physico-chemical parameters like Air temperature, Water temperature, E. C., pH, Free CO 2 , Alkalinity, Total hardness, Calcium hardness, Magnesium hardness, Sodium, Potassium, Chlorides, Nitrates, Phosphates, Sulfates and DO of surface water collected from six different sampling sites from Hiranyakeshi River during January 2010 to December 2010. During this period seasonal variation were observed in all the parameters from all sampling sites and found within the limits of WHO standards except at Site V. Electric conductivity at Site VI during winter and summer season were exceeding limits of WHO standards. Total hardness at Site V considerably increased than that of other Sites. Concentration of Chlorides was also considerably high at Site V in all seasons which are indication of pollution. Over all it has been concluded that Site V is considerably polluted than that of all other Sites.